The success rate of zygomatic implant in oro-facial reconstructive surgery: A systematic review - Gebretsadik, Heron Gezahegn (Orapuh Journal, 2021)
Dental implants are widely used in oro-facial rehabilitation. They are considered effective and acceptable in the replacement of lost teeth and, with implant-supported prosthesis, oro-facial soft and hard tissues configuration. A zygomatic implant is a class of dental implant, which is different from the conventional one, mainly, because it is much longer and attached to the zygomatic bone instead of the maxillary bone. This systematic review was aimed at describing the success rate of the zygomatic implant in oro-facial reconstructive surgery. A review of published literature with no time limitation was conducted in November 2019. An electronic search of PubMed, ISI Web of Science, Cochrane, and Google Scholar databases was conducted to obtain information for this review. A total of 52 prospective and retrospective studies that contained relevant information were selected for data extraction and analysis. Based on the information obtained from the included articles, a total of 3613 zygomatic implants were placed in 1679 study participants. This translates to 2.2 implants being placed per single cohort. After an average follow-up period of 3.5 years, 2.4% of the implants were reported to have failed. Consequently, the success rate of the zygomatic implant was 97.6%. This review has indicated that the zygomatic implant technique is predictable with a high success rate and satisfactory clinical outcomes. Despite the high success rate indicated in this study, conducting randomized controlled/clinical trials to test the efficacy of this implant in comparison with the other technique to treat similar deficits in the oro-facial region (bone grafting) is crucial. Thus, the findings reported in this review must be interpreted with considerable caution. Moreover, more studies with longer follow-up periods involving an adequate number of zygomatic implants placement are imperative. These will help to procure a better understanding of the success rate of zygomatic implants.